Tree Diversity in Tropical Moist Deciduous Forests of Gorumara National Park, India - Mallick, Debanshu; Dasgupta, Subhajit; Paul, Payel; Mondal, Sujit; Pal, Aaratrik; Chowdhury, Monoranjan (Indian Forester, 2022)
Exploration of the diverse tree species in moist deciduous forests is the urgent need to conserve and restore the degraded forest ecosystem in this sub-Himalayan Terai-Duars part of Eastern India. From Red Data Book and IUCN Red List their threatened status and diversity in the unique ecosystem of Gorumara National Park (GNP), India, were assessed carefully to develop baseline data for natural resource study that will help to prepare a master plan for proper conservation of the sustainable ecosystem of the national park. The study used random sampling in different seasons in various microhabitats within the National Park. The diversity of trees was observed, with 315 taxa representing 198 genera belonging to 61 families. Phytosociology and diversity of the tree layer was also analysed through quadrate sampling. The study reflects very rich tree diversity in the area, with 211 species of wild medicinal plants and NTFP species frequently used in indigenous medicine systems and other uses by locals. The study also reveals that the forest provides a unique environment for wildlife by maintaining an ideal ecosystem and acting as a wildlife corridor by connecting several nearby forest landscapes.